(untitled) (Studia Prawnicze / The Legal Studies, 2017)
Prawnofinansowy status Agencji Nieruchomości Rolnych jest złożony. Prawa i obowiązki finansowe natury publicznej przeplatają się z licznymi upraw-nieniami i obowiązkami sfery prywatnoprawnej, zarówno o charakterze materialnym, jak i proceduralnym. W strukturze uprawnień i obowiązków prawno-finansowych da się wyodrębnić sferę podstawową oraz instrumentalną, zaś samą Agencję, m.in. z uwagi na sploty kompetencji publicznoprawnych oraz uprawnieńi obowiązków prywatnoprawnych, należy zaliczyć do podmiotów o charakterze bierno-czynnym. The legal-financial status of the Agricultural Property Agency is complex. Rights and obligations of the financial nature of the public are interspersed with numerous powers and duties of the sphere of private law. Specific elements shaping financial status Agency are organizational relationship and the capital of other legal entities, including primarily with the Treasury and the companies controlled by the Agency. They occur in the context of normative pass Agency to the public finance sector and its companies to the category of public sector entities. In view of the takeover by the executive agencies, a significant part of the tasks previously performed by the state without legal personality, budgetary establishments, precisely in this area normative appeared completely unique opportunity to examine the impact of the construction of legal personality to changes in the shape of subjectivity.